Microsatellite analysis reveals high genetic diversity but low genetic structure in Ethiopian indigenous cattle populations - Dadi, H.; Tibbo, Markos; Takahashi, Y.; Nomura, K.; Hanada, H.; Amano, T. (Wiley, 2008)
Ethiopian cattle are under threat from uncontrolled mating practices and are at high risk of becoming genetically homogeneous. Therefore, to evaluate genetic diversity, population structure and degree of admixture, 30 microsatellite markers were genotyped using 351 DNA samples from 10 Ethiopian cattle populations and the Holstein breed. The mean number of alleles per cattle population ranged from 6.93 +/- 2.12 in Sheko to 7.50 +/- 2.35 in Adwa. The mean observed and expected heterozygosities were 0.674 +/- 0.015 and 0.726 +/- 0.019 respectively. Ethiopian cattle populations have maintained a high level of within-population genetic differentiation (98.7%), the remainder being accounted for by differentiation among populations (1.3%). A highly significant deficiency in heterozygotes was detected within populations (F(IS) = 0.071; P < 0.001) and total inbreeding (F(IT) = 0.083; P < 0.001). The study populations were highly admixed but distinct from pure Bos taurus and Bos indicus breeds. The various levels of admixture and high genetic diversity make Ethiopian cattle populations suitable for future genetic improvement and utilization under a wide range of agro-ecologies in Ethiopia.